Model of Human Resource Management Based on Strengthening The Role of Women in Economics and Politics - Ventje Jeffry Kuhuparuw; Isdairi; Hardilina; Martinus; Syarifah Nurma Afhiani; Elyta Elyta (Cita Konsultindo Research Center, 2023)
This study was written to reconstruct a human resource management paradigm centered on enhancing women's economic and political roles. The library research method was used to construct this article, with a qualitative approach to data collection relevant to the research object. This paper covers the role of women in economic and political spheres, as well as the barriers they face. One of the impediments to women's empowerment is the patriarchal nature of Indonesian culture. Several recommendations for strengthening human resources based on increasing women's economic and political participation include: (1) education and training; (2) access to resources; (3) legal protection; (4) political participation; (5) funding; (6) cooperation; (7) networking and coalitions; (8) community sensitization; and (9) monitoring and evaluation.